Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Melalui Penerapan Metode Problem Based Learning Di Kelas Iii Fase B SDN 10 Sengoret - Anastasia Sutarni (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Classroom Action Research entitled Improving Learning Outcomes in Religious Education and Character through the Application of PBL Methods in Class III Phase B of SDN 10 Sengoret was carried out to improve the learning outcomes of students in class III phase B of SD Negeri 10 Sengoret, Parindu District, Sanggu Regency. The research was carried out by applying the Problem Base Learning (PBL) learning method. PBL is problem-based learning with a teaching model characterized by real problems as a context for students to learn critical thinking and problem-solving skills and gain knowledge (Aris Shoimin 2014). Meanwhile, according to Kamdi (2007), the Problem Based Learning Model is defined as a learning model that involves students trying to solve problems through several stages of the scientific method so that students are expected to be able to learn knowledge related to the problem and at the same time students are expected to have skills in solving problems. The research was carried out in two cycles with the results of an increase in learning outcomes as indicated by an increase in the percentage of students completing both classically and personally.